Respuesta :
We can compare coordinates of points and their images ,and
we need to find the rule
(x, y) ------> (x', y')
A(-5,1)----->A'(-6,0)
-5+a=-6, a=-1, x--->x' , x-1=x'
1+b=0, b=-1, y----->y', y-1=y'
B(-2,7) --------> A'(-3,6)
-2+a= -3, a=-1 , x--->x' , x-1=x'
7+b=6, b=-1, y----->y', y-1=y'
C(0,1) ----->C'(-1,0)
0+a= -1, a=-1 x--->x' , x-1=x'
1+b=0, b=-1 , y----->y', y-1=y'
Now we can see that (x, y)------> (x-1,y-1) Answer A
we need to find the rule
(x, y) ------> (x', y')
A(-5,1)----->A'(-6,0)
-5+a=-6, a=-1, x--->x' , x-1=x'
1+b=0, b=-1, y----->y', y-1=y'
B(-2,7) --------> A'(-3,6)
-2+a= -3, a=-1 , x--->x' , x-1=x'
7+b=6, b=-1, y----->y', y-1=y'
C(0,1) ----->C'(-1,0)
0+a= -1, a=-1 x--->x' , x-1=x'
1+b=0, b=-1 , y----->y', y-1=y'
Now we can see that (x, y)------> (x-1,y-1) Answer A